2015
DOI: 10.14202/vetworld.2015.1230-1236
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antigout activity of Phyllanthus emblica fruit extracts on potassium oxonate-induced gout rat model

Abstract: Aim:The present study has been conducted to evaluate antigout activity of aqueous and alcoholic extracts of Phyllanthus emblica fruits following its 28 days repeated oral administration on potassium oxonate-induced gout rat model.Materials and Methods:The study was conducted on 42 male Sprague-Dawely rats dividing them in seven groups having six rats in each group. Groups I, II, and III served as vehicle control group, gout control group, and standard treatment control group, respectively. Rats of all the grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 21 publications
3
14
0
Order By: Relevance
“…These present results are consistent with other findings [29]. Elevation in xanthine oxidoreductase activity and lowering in superoxide dismutase activity, were observed in the intestine of mice exposed to whole-body gamma irradiation, which, however, reverted back to those levels of controls, when animals were fed triphala (a herbal formulation containing EO fruits) for 7 days prior to irradiation.…”
Section: Resultssupporting
confidence: 93%
“…These present results are consistent with other findings [29]. Elevation in xanthine oxidoreductase activity and lowering in superoxide dismutase activity, were observed in the intestine of mice exposed to whole-body gamma irradiation, which, however, reverted back to those levels of controls, when animals were fed triphala (a herbal formulation containing EO fruits) for 7 days prior to irradiation.…”
Section: Resultssupporting
confidence: 93%
“…Several in vivo studies have demonstrated a reduction of serum uric acid levels in hyperuricemic rats. For example, administration of aqueous and alcoholic extracts of Phyllanthus emblica (200 and 400 mg/kg) reduced serum uric acid and xanthine oxidase enzyme levels in hyperuricemic rats while allopurinol was more potent in inhibiting xanthine oxidase enzyme (Sarvaiya et al, 2015 ). Similar results have also been reported by El-Rahman and Abd–Elhak ( 2015 ) for Allium ampeloprasum, Apium graveolens , and P. crispum using albino rats, where both extracts significantly reduced serum uric acid and lipid peroxidation and increased antioxidant enzyme activity levels at a dose of 5 g/kg.…”
Section: Discussionmentioning
confidence: 99%
“…The maximal treatment dose of SRE in mice was set at 500 mg/kg, which showed a remarkable reduction in serum uric acid in male rats. Potassium oxonate was employed to induce gout mediated by the inhibition of uricase, according to a previous report (18). Here, we used male mice to investigate antihyperuricemia, because endogenous reproductive hormones during the menstrual cycle largely affect uric acid levels (24).…”
Section: Methodsmentioning
confidence: 99%
“…Although allopurinol, a XO inhibitor, and benzbromarone, an inhibitor of protein transporter of urate (URAT1) are considered safe first-line drugs in gout, side effects such as liver toxicity, gastrointestinal disorders, and skin rash can occur (17). To describe the potential of SRE against hyperuricemia, the effect of SRE on serum UA, serum creatine, urinary UA, and urinary XO activity were determined in potassium oxonate (PO)-induced gout mice (18,19). In addition, the histological evaluation of the kidney was conducted to identify the beneficial role of SRE on PO-induced kidney injury in mice.…”
Section: Introductionmentioning
confidence: 99%